Hijacking Democracy in Asia Challenges for Socialpreneurship and Institutional Resilience - Magno, Marito; Costa, Americo da; Carvalho, Salustiano Quintao da; Loe, Domingos (Pandawan, 2025)
The democratization process in Asia faces significant challenges, particularly in leadership transitions often exploited by political elites to maintain power. This phenomenon, known as hijacking democracy, occurs when transitions meant to strengthen democracy are instead manipulated to consolidate authoritarianism and suppress political opposition. This study identifies key factors contributing to democracy hijacking, including political elites, military influence, weak institutions, local political culture, media control, and international pressure. Using a comparative approach across Asia, the research highlights how these elements interact, leading to democratic backsliding and eroding public trust in governance. This issue directly aligns with SDGs 16: Peace, Justice, and Strong Institutions, which emphasizes transparent governance, political participation, and institutional integrity. Ensuring fair and accountable leadership transitions is crucial for sustainable development, social stability, and the protection of democratic values in the region. Without institutional reforms and active civic engagement, democracy in Asia remains vulnerable to manipulation by undemocratic actors.